REPRODUCTIVE BIOLOGY OF FRESHWATER CRAB, PARATELPHUSA SPINIGERA, WOOD MASON (CRUSTACEA-DECAPOD A) - Kaur, Navita; Islam, Rabiul; Besra, Suhasini; Pandey, P. N. (Journal of Indian Fisheries Association, 2006)
This study was aimed to analyze the annual reproductive cycle of thefreshwater crab Paratelphusa spinigera (Wood Mason, 1871). P. spinigera breeds only once in a year; hence, it is a monovoltine species. Gonad maturation, changes in abdomen shape, size and female maturity index (FMI) marked the onset of sexual maturity of female P.spinigera. The occurrence of berried females marked the onset of breeding season. The fecundity of P. spinigera ranged from 533 to 1306 in number, with an average of 699.11 ± 217.38. The correlation of fecundity with carapace width and body weight was also found to be positively significant (r = 0. 780 and 0.933, respectively). The eggs were carried on the pleopods and nurtured for approximately 30-35 days, until the eggs hatch, showing perfect maternal care. The FMI values ranging between 0. 70 and 0.80 represented immature stage of gonadal development. When the FMI ranged from 0.91 to 1.00, all stages of gonadal development, i.e., developing, maturing and mature stages were observed. The females with fully ripe ovary had FMI values greater than 1.00. Keywords·: Female maturity index, fecundity, gonadal development